Product Design of Surabaya City Park Bench with The Development of The Concept Of 5 Ergonomic Attributes - Yosef Richo; Desita Rizky Amelia; Duta Pemadani (Faculty of Civil Engeneering and Planning - ITATS, 2022)
Parks have an important role for residents of the city of Surabaya, in addition to functioning as a place of relaxation, parks also have various important roles such as as a source of city lungs, family recreation facilities, entertainment, health, and sports to sharing knowledge and culture. Park Bench is one of the important facility products that can increase the value of satisfaction in the minds of visitors. The research here tries to explore further the design of the park bench by looking at the suitability of various aspects to support the comfort and safety of its use. In this study, trying to harmonize the design of park benches by developing the concept of comfort and safety on ergonomic standards, first, the researchers studied and analyzed the existing conditions of several parks in the city of Surabaya and also analyzed the sources of supporting literature. Existing in this study took several samples of city park benches that matched the criteria to be used as subjects in the study, the two researchers then analyzed the criteria for developing product design management by looking at the needs of the user aspects by combining them with the suitability of Ergonomics standards. Furthermore, the researchers also tried to look at other supporting attributes in supporting the level of comfort and safety of park benches such as product quality consisting of aesthetics and functionality. The three researchers carried out data processing and calculations for calculating ergonomic values that could be applied to product design. The research here is expected to be able to understand more deeply related to the development of the Surabaya city park bench design by applying the comfort and safety attributes in more detail and also to understand the standard characteristics that can be applied to the next park bench product design.